Testing Construct Validity of Competency Indicators of Scientific Literacy in Junior Secondary Students - Chayada Jomtarak; Peerawut Suwanjan; Phadungchai Pupat; Rangsan Jomtarak (My University, 2019)
Abstract This research aimed to check the construct validity of competency indicators of scientific literacy in junior secondary students. The steps for conducting the research included a sample of 392 persons, derived from stratified random sampling, from a population of 22,855. The instrument used in this research is a measurement tool with a reliability of 0.838. Statistical analysis includes confirmatory factor analysis, mean, standard deviation, and one-way analysis of variance. The study results found that scientific literacy indicators of junior secondary students had construct validity by taking into consideration Chi-square = 20.842, df = 17, p = 0.233 and X 2 / df = 1.226. which was less than 2, while RMSEA = 0.024, RMR = 0.07, which was near to 0, GFI = 0.987, AGFI = 0.972, CFI = 0.979.
Keywords: Stratified Sampling; Validity; Sample (material); Scientific Literacy; Educational Methods and Outcomes